Microsurgical Air-Jet Dissector System: Effective Dissection and Gentle and Remote Creation of Working Space. Issue 3 (August 2016) - Okada, Tomu; Fujitsu, Kazuhiko; Ichikawa, Teruo; Miyahara, Kousuke; Tanino, Shin; Uriu, Yasuhiro; Hataoka, Syunsuke; Tanaka, Yuusuke; Suzuki, Kouji
Abstract : Background: Many retraction methods and surgical devices have been developed for various situations. However, there are still times when it is difficult to perform retraction during surgery using these techniques or devices. Objective: To describe a new device and a surgical technique that the authors have used successfully to aid in tissue retraction. Methods: We have developed a microsurgical air-jet dissector system comprising a Fukushima sucker (1 to 5 L), extension tube, elastic tape to connect the sucker to the tube, glass-in filter, fibrin glue spray tube, and carbon dioxide(CO2 ) cylinder. Air-jet force is controlled in 3 ways: (1) the pressure meter on the cylinder; (2) teardrop hole on the sucker; and (3) distance between the sucker tip and target structure. We also made a "side-hole" sucker for air-jet dissection on a plane tangential to the surgeon's line of sight. The system is applied in either "remote use" or "contact use." "Remote use" means that the device is used 1 to 20 mm distant from the target structure to provide a suitable working space created by the air-jet pressure, which gently retracts and displaces the surrounding structures. Conversely, "contact use" is effective to dissect strong adhesion between tumors and normal neurovascular structures. Results: Combined usage with a sucker allows this system to be used to clear the surgical field and help the surgeon to retraction and identify exact bleeding points. Conclusions: This microsurgical air-jet dissection system is a useful device to retract and clean the surgical field safely and cheaply.